Are white-collar prisoners special? Prison adaptation and the special sensitivity hypothesis. (November 2021) - Long, Joshua; Logan, Matthew W.; Morgan, Mark A.
Abstract: Objectives: This study examines the behaviors of people convicted of white-collar offenses to determine if white-collar prisoners are truly distinct from those who were found guilty of other types of offenses. Method: Using data from a large Midwestern state we identified 1867 prisoners convicted of white-collar offenses and compared them to 55, 756 prisoners who were not convicted of white-collar offenses. Binary logistic regression models were used to control for the effects of potential confounders. The likelihood of being found guilty of various types of misconduct and forms of recidivism were calculated. Results: White-collar prisoners were found to have significantly different characteristics than other types of prisoners, but the multivariate models found that they were not significantly different in terms of their likelihood of being found guilty of most types of misconduct (i.e., resistance to orders, property misconduct, drug-related misconduct, or other misconduct). White-collar prisoners were not more or less likely to return to prison for any reason. The only significant distinction between white-collar prisoners and other types of prisoners was their reduced likelihood of being found guilty of violent misconduct. Highlights: White-collar offenders tend to have different personal characteristics than other prisoners in state facilities. White-collar offenders are less likely to be found guilty of violent misconduct in prison. White-collar offenders are not more or less likely to return to prison after release than other types of prisoners.